A Very Rare Reason for Hyperandrogenism: Adrenal Tumor Case - Nurşen Kurtoğlu Aksoy; Hakan Gürarslan; Gül Gizem Pamuk (Bagcilar Medical Bulletin, 2023)

(untitled)
Adrenal tumors are very rare causes of hyperandrogenism. Androgensecreting adrenal tumors are usually malignant; however, benign tumors have also been described in women. Adrenocortical carcinoma is very rare with incidence of 1 2 million per year. The androgen secreting type of adrenocortical carcinoma can be presented with hirsutism, acne, alopecia and virilization symptoms such as cliteromegaly. This case was presented with hyperandrogenism and virilization symptoms and it was diagnosed as having a very rare cause, namely androgen secreting adrenal tumor. Because the symptoms are related to gynecological complaints such as menstrual irregularities and cliteromegaly, these patients would first need to apply to their gynecologists, who may play an important role in the early diagnoses of these rare diseases.